Structure and genesis of the Brzuchowo Lake - Kamien Krajenski Esker - Krupa, Adam (Journal of Education, Health and Sport, 2016)
The paper presents the morphology and geology of the Esker Lake Brzuchowo - Stone Krajeński. Particular attention was paid to the sedimentological record in esker sediments, which is important to determine the conditions of its creation.